Influence of different thermoplastic polymer/wood ratios on the mechanical and thermal properties of composite materials. (2017) - Bessa, João; Mota, Carlos; Cunha, Fernando; Fangueiro, Raul
Abstract: This work compares the influence of different thermoplastic polymer/wood powder ratios on the mechanical and thermal properties of composite materials. These mass ratios were varied between 70:30 and 50:50, respectively. Moreover, the effect of a coupling agent incorporation, namely maleic anhydride polypropylene (MAPP), to promote better adhesion between both components, on these properties was evaluated. The composite materials were obtained by compression moulding process. The mechanical tests were subsequently performed to evaluate the tensile, flexural and impact properties. Besides that, the thermal properties were obtained using an Alambeta testing device. The experimental results show that the wood powder has the capacity to reinforce the thermoplastic polymer used, polypropylene (PP). The increase of mass fraction of wood powder on the final composite materials allows better mechanical properties, such as Young's and flexural modulus. Comparing the composite materials with 70:30 and 50:50 ratios, it was verified the improvement of Young's modulus by 1773 MPa to 2808 MPa, and flexural modulus by 1569 MPa to 1739 MPa. In the other hand, it was also verified that this trend contributes to the slight decrease on the thermal conductivity, namely from 0.145 W m -1 K -1 to 0.141 W m -1 K -1, respectively. The 2% MAPP incorporation leads to an even higher increase of the mechanical properties, namely in the Young's modulus to 3320MPa, with 50:50 ratio. However, despite this trend, the same was not verified on the thermal conductivity, which increases to 0.145 W m -1 K -1 . These results allow to conclude that the increase of wood powder can increase the mechanical properties of the PP composites, and the MAPP incorporation contributes to the better compatibility between both materials, increasing also these properties.